Methodology of hydrogen embrittlement study of long-term operated natural gas distribution pipeline steels caused by hydrogen transport - Hryhoriy Nykyforchyn; Olha Zvirko; Myroslava Hredil; Halyna Krechkovska; Oleksandr Tsyrulnyk; Oleksandra Student; Leonid Unigovskyi (Fracture and Structural Integrity)
A methodology of experimental research on hydrogen embrittlement of pipe carbon steels due to the transportation of hydrogen or its mixture with natural gas by a long-term operated gas distribution network is presented. The importance of comparative assessments of the steel in the as-received and operated states basing on the properties that characterize plasticity, resistance to brittle fracture and hydrogen assisted cracking is accentuated. Two main methodological peculiarities are pointed out, (i) testing specimens should be cut out in the transverse direction relative to the pipe axis; (ii) strength and plasticity characteristics should be determined using flat tensile specimens with the smallest possible thickness of the working part. The determination of hydrogen concentration in metal, metallographic and fractographic analyses have been supplemented the study. The effectiveness of the proposed methodology has been illustrated by the example of the steel research after its 52-year operation.